Alissa Gigliotti: capstone - Gigliotti, Alissa, artist (Colorado State University. Libraries, 2013)
The artist's statement: Along with science, I have always had a strong interest in the fine arts, particularly scientific illustration and graphic art. My background is in aquatic biology but I think and interpret visually. I'm also drawn to the arts for their potential as a means for communication and expression. I find that graphic design and illustration provide me with a way to convey my artistic and scientific passion through visual communication while offering a balance between the technical and creative.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.